Evaluation of the Impact of Ruminant Trans Fatty Acids on Human Health: Important Aspects to Consider. Issue 12 (9th September 2016) - Kuhnt, Katrin; Degen, Christian; Jahreis, Gerhard
Abstract : The definition and evaluation of trans fatty acids (TFA) with regard to foodstuffs and health hazard are not consistent. Based on the current situation, the term should be restricted only to TFA with isolated double bonds in trans-configuration. Conjugated linoleic acids (CLA) should be separately assessed. Ideally, the origin of the consumed fat should be declared, i.e., ruminant TFA (R-TFA) and industrial TFA (non-ruminant; I-TFA). In ruminant fat, more than 50% of R-TFA consists of vaccenic acid (C18:1 t11). In addition, natural CLA, i.e., c9, t11 CLA is also present. Both are elevated in products from organic farming. In contrast to elaidic acid (t9) and t10, which occur mainly in partially hydrogenated industrial fat, t11 is partially metabolized into c9, t11 CLA via Δ9-desaturation. This is the major metabolic criterion used to differentiate between t11 and other trans C18:1. t11 indicates health beneficial effects in several studies. Moreover, CLA in milk fat is associated with the prevention of allergy and asthma. An analysis of the few studies relating to R-TFA alone makes clear that no convincing adverse physiological effect can be attributed to R-TFA. Only extremely high R-TFA intakes cause negative change in blood lipids. In conclusion, in most European countries, the intake of R-TFA is assessed as being low to moderate. Restriction of R-TFA would unjustifiably represent a disadvantage for organic farming of milk.